2017
DOI: 10.1161/jaha.117.007270
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Ablation of the AV Junction in Patients With Atrial Fibrillation: Impact of Cardiac Resynchronization Therapy

Abstract: BackgroundPatients with atrial fibrillation (AF) often undergo AV junction ablation (AVJA) and pacemaker implantation. Right ventricular (RV) pacing contributes to increased risk of heart failure (HF), which may be mitigated by biventricular pacing. We sought to determine the impact of AVJA concurrent with RV versus biventricular pacemaker implantation on AF and HF hospitalizations.Methods and ResultsThe MarketScan Commercial and Medicare Supplemental claims database was used to select 18‐ to 100‐year‐old pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Finally, in a nationwide cohort similar to that used in the current study, over 4 years of follow-up, pacemaker patients with AF and concurrent AVJ ablation were associated with a significantly increased risk of HF hospitalization compared with matched pacemaker patients without an ablation. 22 Our data and the echocardiographic data from the PACE trial are consistent in demonstrating a relatively rapid detrimental effect of RV pacing on ventricular function, which can be discerned within the first several months. Although the mechanisms of this observed effect have not been fully elucidated, an acute analysis of 12 patients with normal LVEF and forced RV pacing using short AV delays demonstrated a significant drop in LVEF within 2 hours of RV pacing and progressive deterioration of ventricular function after a week of RV pacing.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, in a nationwide cohort similar to that used in the current study, over 4 years of follow-up, pacemaker patients with AF and concurrent AVJ ablation were associated with a significantly increased risk of HF hospitalization compared with matched pacemaker patients without an ablation. 22 Our data and the echocardiographic data from the PACE trial are consistent in demonstrating a relatively rapid detrimental effect of RV pacing on ventricular function, which can be discerned within the first several months. Although the mechanisms of this observed effect have not been fully elucidated, an acute analysis of 12 patients with normal LVEF and forced RV pacing using short AV delays demonstrated a significant drop in LVEF within 2 hours of RV pacing and progressive deterioration of ventricular function after a week of RV pacing.…”
Section: Discussionsupporting
confidence: 80%
“…For patients with the same indications, biventricular pacing was only reported to result in a slight increase in LVEF (3.3%‐6.6%) . Compared to right ventricular pacing, biventricular pacing was associated with significant improvement in symptoms, but not 6‐min walk distance or overall mortality . Since no comparative study between HBP and biventricular or right ventricular pacing has been reported, we cannot draw any conclusion on the superiority of HBP over biventricular pacing at the present time.…”
Section: Discussionmentioning
confidence: 77%
“…20 Compared to right ventricular pacing, biventricular pacing was associated with significant improvement in symptoms, but not 6-min walk distance or overall mortality. 21 Since no comparative study between HBP and biventricular or right ventricular pacing has been reported, we cannot draw any conclusion on the superiority of HBP over biventricular pacing at the present time. Another population that could potentially benefit from HBP is heart failure patients with PR prolongation and narrow QRS com-plex.…”
Section: Discussionmentioning
confidence: 78%
“…It and can also decrease the number of HF hospitalizations. 132,133 Advanced treatment for heart failure…”
Section: Cardiac Resynchronization Therapymentioning
confidence: 99%